Coincident In Vitro Analysis of DNA-PK-Dependent and -Independent Nonhomologous End Joining. (29th June 2010) - Hendrickson, Cynthia L.; Purkayastha, Shubhadeep; Pastwa, Elzbieta; Neumann, Ronald D.; Winters, Thomas A.
Abstract : In mammalian cells, DNA double-strand breaks (DSBs) are primarily repaired by nonhomologous end joining (NHEJ). The current model suggests that the Ku 70/80 heterodimer binds to DSB ends and recruits DNA-PK cs to form the active DNA-dependent protein kinase, DNA-PK. Subsequently, XRCC4, DNA ligase IV, XLF and most likely, other unidentified components participate in the final DSB ligation step. Therefore, DNA-PK plays a key role in NHEJ due to its structural and regulatory functions that mediate DSB end joining. However, recent studies show that additional DNA-PK-independent NHEJ pathways also exist. Unfortunately, the presence of DNA-PK cs appears to inhibit DNA-PK-independent NHEJ, and in vitro analysis of DNA-PK-independent NHEJ in the presence of the DNA-PK cs protein remains problematic. We have developed an in vitro assay that is preferentially active for DNA-PK-independent DSB repair based solely on its reaction conditions, facilitating coincident differential biochemical analysis of the two pathways. The results indicate the biochemically distinct nature of the end-joining mechanisms represented by the DNA-PK-dependent and -independent NHEJ assays as well as functional differences between the two pathways.